2020
DOI: 10.3389/fncel.2020.576650
|View full text |Cite
|
Sign up to set email alerts
|

Gas6 Inhibits Toll-Like Receptor-Mediated Inflammatory Pathways in Mouse Microglia via Axl and Mer

Abstract: Background: Microglia are well known key regulators of neuroinflammation which feature in multiple neurodegenerative disorders. These cells survey the CNS and, under inflammatory conditions, become "activated" through stimulation of toll-like receptors (TLRs), resulting in changes in morphology and production and release of cytokines. In the present study, we examined the roles of the related TAM receptors, Mer and Axl, and of their ligand, Gas6, in the regulation of microglial pro-inflammatory TNF-α productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…Our data suggested that OPN secreted by Muller and microglia could suppress TNF activation to impede excessive activation of microglia. Similarly, our data showed that GAS6 mediated cell-cell communication between amacrine and microglia was enhanced by hyperglycemia, and negatively regulated the pro-inflammatory via TAM receptors, Axl and Mer (Gilchrist et al, 2020; Figure 3E). CellChat predicted that hyperglycemia-induced GAS6 signaling was mediated by ligand GAS6 and both two receptors (Figure 3D), Ligand GAS6 was upregulated in microglia and amacrine, whereas the receptors were up-regulated in microglia (Figure 3F).…”
Section: Communication Between Microglia and Retinal Cells Is A Potential Feedback To Suppress The Excessive Activation Of Microgliasupporting
confidence: 75%
“…Our data suggested that OPN secreted by Muller and microglia could suppress TNF activation to impede excessive activation of microglia. Similarly, our data showed that GAS6 mediated cell-cell communication between amacrine and microglia was enhanced by hyperglycemia, and negatively regulated the pro-inflammatory via TAM receptors, Axl and Mer (Gilchrist et al, 2020; Figure 3E). CellChat predicted that hyperglycemia-induced GAS6 signaling was mediated by ligand GAS6 and both two receptors (Figure 3D), Ligand GAS6 was upregulated in microglia and amacrine, whereas the receptors were up-regulated in microglia (Figure 3F).…”
Section: Communication Between Microglia and Retinal Cells Is A Potential Feedback To Suppress The Excessive Activation Of Microgliasupporting
confidence: 75%
“…Among these molecules, high mobility group box 1 (HMGB1) protein appears in the early stages of stroke and is recognized by several toll-like receptors (TLRs) like TLR2 or TLR4, which trigger an inflammatory response through the release of pro-inflammatory cytokines in an NF-κB-dependent process. In fact, TLR4 blockade has shown to be protective against brain ischemia with a reduction of the infarcted area, which could be due to a decrease in pro-inflammatory cytokines secreted by microglia [ 45 ]. Peroxiredoxins (Prdxs) constitute another important group of DAMPs with redox-activity.…”
Section: Microgliamentioning
confidence: 99%
“…Notably, previous studies have revealed that Lgals3 (Galectin 3) inhibition attenuates pain after nerve injury (Ma et al, 2016), Grn (Granulin) promotes peripheral nerve regeneration (Lim et al, 2012), Apoe polymorphisms are related to severity of peripheral neuropathy (Monastiriotis et al, 2013; Monastiriotis et al, 2012) and Ctsb (Cathepsin B) inhibition attenuates development of allodynia in inflammatory pain (Ma et al, 2016; Sun et al, 2012). Axl (AXL Receptor Tyrosine Kinase) signalling via its ligand growth arrest gene 6 ( Gas6 ) that is also upregulated after CCI, facilitates phagocytosis of apoptotic cells by microglia as well as increasing cellular migration and myelination and reducing apoptosis and toll-like receptor-mediated inflammation (Gilchrist et al, 2020; Goudarzi et al, 2020; Grommes et al, 2008). Bhlhe40 is a transcription factor that regulates myeloid cell activation and inflammation as well as self-renewal (Carey et al, 2020; Jarjour et al, 2019).…”
Section: Discussionmentioning
confidence: 99%